“There are lots of new faces this year… I’m not entirely sure when I became one of the old ones”: a psycho-ethnography of the self at #PoWESconf five years in - Silverio, Sergio A. (Frontiers in Psychology, 2024)
Conferences have been discussed as spaces for academic work to extend beyond the confines of one's institution, fostering environments of collaborative working, learning, and social bond-making. The British Psychological Society's Psychology of Women and Equalities Section hosts an annual conference, attended by feminist scholars from around the world. Drawing on auto-ethnography and psycho-biography, this paper presents a 'psycho-ethnography of the self' with reflections centred on: 'Scholarship', 'Feminist Praxis'; '(Safe) Academic Spaces'; and 'Positioning the Self'. This article contributes to a small, but growing body of literature critically reflecting on conferences as spaces for personal and professional development and academic growth.